Are the Growth Standards of the World Health Organization Valid for Spanish Children? The SONEV Study - Pérez-Bermejo, Marcelino; Alcalá-Dávalos, Luisa; Pérez-Murillo, Javier; Legidos-García, Maria Ester; Murillo-Llorente, Maria Teresa (Frontiers in Pediatrics, 2021)
Background: The use of different growth tables to assess the population’s nutritional status has given rise to a series of limitations arising from the lack of consensus and uniform methodological criteria. This leads to a disparity of results that prevent an accurate and reliable diagnosis of whether a child is overweight or obese. Objective: The purpose of this study was to develop growth references for weight, height, and body mass index for Eastern-Spanish children from 6 to 16 years of age. Methods: The final sample used to fit the growth curves was made up of 1102 observations. The 2007 WHO curves are currently used for Child Health Service Cards. Therefore, to make the comparison of the internal values obtained as realistic as possible, the same construction method has been used for the internal curves, modeling age as a continuous variable and simultaneously adjusting the curves, smoothing them using cubic splines and further smoothing the edge effects by means of data extending above or below the upper and lower age limits. Results: Growth curves for percentiles were constructed for both sexes and higher values were noticeably found to set as growth-standard compared to WHO-standards. Conclusion: Our analysis shows that the WHO 2007 standard references are not suitable for Eastern-Spanish children. The standards shown in this study are much more realistic and current, and we believe that their use will help healthcare professionals more effectively combat the current epidemic of overweight and obesity.